2020
DOI: 10.1007/s00330-019-06626-6
|View full text |Cite
|
Sign up to set email alerts
|

MRI of non-specific low back pain and/or lumbar radiculopathy: do we need T1 when using a sagittal T2-weighted Dixon sequence?

Abstract: Objective To show that for the MRI workup of non-specific low back pain and/or lumbar radiculopathy, the acquisition of T1weighted sequences in the sagittal plane could be waived when using an FSE T2-weighted Dixon sequence. Materials and methods Three musculoskeletal radiologists retrospectively reviewed fifty lumbar spine MRI examinations performed for non-specific low back pain and/or lumbar radiculopathy. Two protocols were separately analyzed in the sagittal plane: a standard protocol (T1-weighted, in-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
0
23
0
2
Order By: Relevance
“…The endplates are vulnerable to suffered from lesions, and termed as the “weak link” of the lumbar spine 8‐10 . Endplates lesions cause considerable reduction in the disk’s proteoglycan and lead to elevated catabolic enzymes and pro‐inflammatory cytokines, resulting in degenerative changes 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…The endplates are vulnerable to suffered from lesions, and termed as the “weak link” of the lumbar spine 8‐10 . Endplates lesions cause considerable reduction in the disk’s proteoglycan and lead to elevated catabolic enzymes and pro‐inflammatory cytokines, resulting in degenerative changes 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a recent meta-analysis of eighteen studies on this topic found a pooled sensitivity, specificity, and AUC of 89% (95% CI: 86, 92%), 88% (95% CI: 85, 91%), and 0.95, respectively [4]. In light of these results, a single FSE T2w Dixon sequence could be used instead of the set of sequences which are usually acquired in the sagittal plane for this indication, as has been previously shown for spine MRI protocols for the detection of metastases or for the workup of non-specific low back pain or lumbar radiculopathy [11,12]. Using a single sagittal FSE Two-by-two differences: no statistical difference between readers (all p > 0.29, Bonferroni corrected significance level p < 0.008) AUC, area under the curve; 95% CI, 95% confidence intervals; +LR, positive likelihood ratio; −LR, negative likelihood ratio; NA, not applicable.…”
Section: Discussionmentioning
confidence: 91%
“…The image sets derived from a T2w Dixon acquisition include in-phase, out-of-phase, fat-only, and water-only. The derived fat-only images offer an additional benefit: they may replace T1-weighted sequences for the study of bone marrow fat in some indications [11,12]. This has allowed the simplification of protocols for several applications, including the detection of bone marrow metastases, sacroiliitis, or for the workup of low back pain and/or lumbar radiculopathy [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study among patients showing various types of vertebral lesions (including recent fractures, spondylitis, metastasis, and haemangioma), a T2-weighted DIXON sequence showed more homogeneous fat suppression and superior lesion conspicuity when compared to imaging using spectral attenuated inversion recovery (SPAIR) [ 17 ]. For the degenerative lumbar spine, previous studies were able to demonstrate that imaging with a single sagittal T2-weighted DIXON sequence could replace the combination of dedicated T1-weighted, T2-weighted, and STIR sequences, which would not be at the expense of worsened diagnostic performance [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%